A definition and review of the Myospila argentata species-group (Diptera: Muscidae: Mydaeinae) from China. (2nd January 2020) - Sun, Cuiying; Wei, Lianmeng
ABSTRACT: The M. argentata species group is proposed within Myospila Rondani to include 2 new and 11 known species from Oriental, Australian, East Palaearctic and Afrotropical regions. A key to all 13 species assigned to the herein newly defined M. argentata species group is provided. The type specimens of two new species are housed in the Wei Lianmeng Model Worker Innovation Studio, Anshun, Guizhou, China (WLMMWISAGC). http://www.zoobank.org/urn:lsid:zoobank.org:pub:58F9C6BA-465A-461B-98BC-19896F78670E